Meningkatkan Kreativitas Peserta Didik Menggunakan Model Project Based Learning Melalui Observasi Lingkungan Sekolah pada Fase A Kelas 1 SDN Sondakan - Stephiana Ari Rita (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aimed to implement Project-Based Learning (PBL) through environmental observation to enhance the creativity and cognitive learning outcomes of first-grade students at SDN Sondakan, Surakarta. This Classroom Action Research (CAR) involved 6 students from the first-grade A phase in the 2024/2025 academic year. The research method involved planning, implementation, observation, and reflection. Data was collected through tests and observations. Qualitative descriptive analysis was used to measure cognitive learning outcomes (written summative tests, project performance success), creativity outcomes, and the learning process (success of implementing the Project-Based Learning model). The results showed a significant increase in students' creativity, producing original ideas (from 79% to 83%), creating original works and actions (from 77% to 81%), and demonstrating flexibility in thinking to find alternative solutions to problems (from 71% to 75%). Cognitive learning outcomes measured through written summative tests in the "Proficient" aspect increased by 100%, from 33.33% to 66.67%. Additionally, cognitive learning outcomes in terms of products or projects showed a 100% increase in the "Proficient" aspect and a 33.34% increase in the "Competent" aspect. The implementation of Project-Based Learning through environmental observation showed an improvement in all stages of the learning model syntax. The "Determining Essential Questions" stage increased by 3.1%, "Designing Project Plans" increased by 3.2%, "Developing" increased by 5.3%, "Monitoring Students and Project Progress" increased by 8.9%, and "Testing Results" increased by 5.3%. Recommendations include strengthening the improvement of learning strategies, enhancing creativity, and evaluating the curriculum to achieve comprehensive student learning outcomes across various domains.